Raindrops (A New Series of Textbooks in English) - Nikalje, Varada M. (THE PRIMARY TEACHER, 2010)
TThe new syllabi and textbooks brought out by NCERT in the wake of NCF-2005 attempt to provide a somewhat equitable representation of rural and urban content, themes and images. However, there are states in India with a large number of rural or tribal children, or children from migrant families living in urban areas, whose exposure to English would be extremely limited. Most of these children are likely to be first generation school-goers, with little or no help from parents and siblings. In the context of English at the primary level, it was felt that rural children deserve an altogether distinctive series of textbooks. Raindrops marks an unprecedented attempt of this kind. The textbooks in this series utilise the insights of modern theories in linguistics to bring home certain concepts to boys and girls studying in village schools: listening exercises have been included, grammar is introduced unobtrusively, and the themes favour the rural world. This article is based on a presentation made at the 14th Joint Review Meeting of Sarva Shiksha Abhiyaan, New Delhi, 22 July 2011.